Pengaruh Promosi dan Harga terhadap Keputusan Pembelian Ayam Penyet Nasi Tutug Oncom Setu Melalui Aplikasi Gofood - Robiatul Adawiyah; Joseph MJ Renwarin; Widi Winarso (Jurnal Manajemen dan Ekonomi Kreatif, 2024)
Tutug Oncom is a small restaurant that sells Tutug Oncom rice in the Bekasi area. This research aims to influence promotions and prices on purchasing decisions for Ayam Penyet Nasi Tutug Oncom via the Gofood application. Using the research method using the Partial Least Square (PLS) quantitative approach via SmartPLS 4.0, data from 100 respondents was analyzed to test the proposed hypothesis. The analysis results show that Gofood promotions, especially through advertising and price discounts, significantly influence purchasing decisions. This shows that effective promotional strategies can increase consumer interest in choosing Ayam Penyet Nasi Tutug Oncom via the Gofood platform. Furthermore, price factors also proved to be important, with price advantages and competitive pricing positively affecting purchase decisions. The managerial implications suggest that companies should consider relevant promotional strategies and competitive pricing to maximize product appeal in the online market. The study also reveals the dominant consumer profile, with the majority of respondents aged 21-25 years, mostly female, and predominantly students. These findings indicate that the younger generation, especially those actively using technology, are the primary target in digital marketing strategies employed by Gofood. This research not only provides insights into the factors influencing purchase decisions in the context of food delivery applications but also offers a foundation for further studies to explore other variables that may affect consumer preferences online.